The Right to Freedom of Religion in The Semedi Ritual at Pesanggrahan Langenharjo - Kuncoro, David Bagus (Universitas Sebelas Maret, 2023)
Freedom to practice religion and belief is a citizen's right guaranteed by the state and has been regulated in various laws and regulations in Indonesia. In the Indonesian constitution itself, the provisions regarding the right to religious freedom are regulated in a separate chapter, namely in chapter XA on Human Rights. The Semedi ritual is a person's human right in terms of religious freedom. One of the places that are sacred and used as a location to carry out the Semedi Ritual is Pesanggrahan Langenharjo which is located in Grogol District, Sukoharjo Regency, Central Java. This study aims to determine the implementation of the right to freedom of religion in Indonesia in the Semedi Rituals at the Pesanggrahan Langenharjo. This research uses empirical research methods that are descriptive. Research data collection techniques used are field studies and literature studies with research data analysis techniques using qualitative methods that use an inductive mindset. The results of this research are it can be seen that the implementation of the right to freedom of religion in Indonesia has been carried out following the applicable laws and regulations.